Combined external quality assessment of cytology and histology opinions: a pilot scheme for a cluster of five laboratories. Issue 9 (September 1984) - Husain, O; Butler, E B; Woodford, F P
Abstract : A cluster of five self selected cytodiagnostic laboratories circulated 70 cervical/vaginal smears and 50 sputum smears in a series of five week cycles. Histological sections related to the abnormal smears were also circulated. Proportions of agreement and disagreement were analysed for cervical and sputum smear reports against the original report (and by implication against the consensus); corresponding calculations were made for the histological reports. Cytological and histological correlation was also examined. Agreement for major categories (benign, intraepithelial neoplasia, malignant) was 87% for cervical cytology and 83% for sputum. When the effect of potential random agreement was compensated for by the use of kappa statistics the values of kappa were +0.79 and +0.65, respectively. The corresponding kappa values for gynaecological and respiratory tract histology were +0.78 and +0.82, respectively. Agreement on finer degrees of abnormality was, predictably, less good. Problems arising in this pilot scheme are discussed and suggestions for a simplified scheme are made.